A Model Investigation of Aerosol‐Induced Changes in the East Asian Winter Monsoon. Issue 16 (30th August 2019) - Liu, Zhen; Ming, Yi; Wang, Lin; Bollasina, Massimo; Luo, Ming; Lau, Ngar‐Cheung; Yim, Steve Hung‐Lam
Abstract: The response of the East Asian winter monsoon (EAWM) circulation to aerosols is studied using a coupled atmosphere‐slab ocean general circulation model. In the extratropics, the aerosol‐induced cooling in the midlatitudes leads to an intensified subtropical jet stream, a deepened East Asian trough, and thus an enhanced EAWM. In the tropics, the local Hadley circulation shifts southward to compensate for the interhemispheric asymmetry in aerosol radiative cooling. Anomalous subsidence at around 10°N leads to a salient anticyclone to the southwest of the Philippines. The associated southwesterlies advect abundant moisture to South China, resulting in local precipitation increases and suggesting a weaker EAWM. The EAWM response to aerosol forcing is thus driven by a competition between tropical and extratropical mechanisms, which has important implications for the future monsoon evolution, as aerosol changes may follow different regional‐dependent trajectories. Plain Language Summary: In this study, we use a global atmospheric model to examine how aerosols affect the East Asian winter monsoon intensity, which modulates the strength of cold air outbreaks in East Asia. The aerosol‐induced cooling mainly appears in the Northern Hemisphere midlatitude land and their downwind ocean regions. The cooling enhances the East Asian winter monsoon north of 30°N, with stronger northerly winds and colder winters there. However, aerosols weaken the East Asian winter monsoon south of 30°N, with intensified southerly winds bringing warm and moist air to South China, thus resulting in enhanced precipitation. The larger magnitude of the southerly south of 30°N than that of the northerly north of 30°N and increased precipitation over South China suggest a considerable influence of aerosols on East Asian winter monsoon through tropical circulation changes. Key Points: Anthropogenic aerosols enhance the East Asian winter monsoon circulation north of 30°N but weaken it south of 30°N The precipitation increases over South China are primarily associated with an anomalous anticyclone to the southwest of the Philippines The tropical circulation changes are related to a southward shift of the local Hadley circulation driven by asymmetrical aerosol forcing